IPrognostic factors for idiopathic pulmonary fibrosis: clinical, physiologic, pathologic, and molecular aspects - Lee, S.H.; Shim, H.S.; Cho, et al., S.H. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: Previous studies identified clinical and physiologic factors of idiopathic pulmonary fibrosis (IPF) that are related to an increased risk of mortality. But there are few studies about histologic and molecular approach. Objective:We investigated whether the C-reactive protein (CRP), fibroblastic foci, phosphorylated Smad2/3 (p-Smad2/3), tumor growth factor-β (TGF-β),TGF-β receptor II (TβRII), and the polymorphism of the TGF-β1 codon 10 are associated with the progression of IPF patients. Design: Eighty-six IPF patients who underwent surgical lung biopsies were examined. For each patient, clinical and physiologic parameters were investigated, and we performed immunohistochemical staining for p-Smad2/3 and TβRII, and genotyping of the TGF-β1 codon 10 polymorphism. Results: Age at diagnosis, gender, symptom duration, and smoking status did not show a significant association.However, the amount of smoking (p = 0.002), severe reduction in the percentages of predicted forced vital capacity (p = 0.013) and diffusion lung capacity of carbon monoxide (p = 0.023), CRP (p = 0.009) at diagnosis, and fibroblastic foci (p = 0.026) were associated with a poor prognosis. Cellularity, fibrosis, expression level of p-Smad2/3 and TβRII, and genotype of the TGF-β1 codon 10 polymorphism did not have a statistically significant association with the prognosis. Conclusion: This study confirmed the amount of smoking, abrupt decrease in follow-up pulmonary function parameters, fibroblastic foci, and increased levels of CRP concentration at diagnosis were significantly associated with poor survival. Larger studies are required to confirm all prognostic factors including CRP.